Trends in research on digital internationalization of SMEs: A bibliometric analysis - Sáenz De Viteri Anzules, Cristian Roosevelt (2026)
The intersection of digitalization and the internationalization of Small and Medium-sized Enterprises (SMEs) constitutes a critical and rapidly evolving research area. This study aims to map the intellectual structure and trends of the scientific literature on this topic to identify consolidated research focuses and significant gaps. To this end, a bibliometric analysis of 149 publications indexed in Scopus (period 2007-2025) was conducted. Data were processed using the Bibliometrix R package and the Biblioshiny tool to perform keyword co-occurrence analysis and thematic mapping. The findings reveal a consolidated research base around the concepts of "internationalization," "digitalization," and "SMEs," with notable growth since 2020. "Digital transformation," "digital platforms," and "dynamic capabilities" emerge as motor themes. The analysis highlights two key structural gaps in the literature: the limited integration of "sustainability" and, most notably, the absence of "public management" as a central research axis. It is concluded that while the literature recognizes digitalization as a driver for SME internationalization, the current focus neglects crucial dimensions such as public support policies and sustainability, presenting a clear opportunity for future research.